Boosting Smart Building Energy Saving Capacity using Phase Change Materials - Kheradmand, Mohammad; Javadi, Sara; Lü, Xiaoshu (IEEE, 2020)
Energy consumption in buildings accounts for over 30% of the total energy use in the world, so it is a priority in the EU. Phase change materials (PCMs) can assist for thermal regulation, because they can save and release the heat. In smart buildings, consumers can incorporate in managing building energy systems, by Demand Response Programs (DRPs). One applicable method is to include PCM as interior coating. Two groups of tests in a test house are investigated concerning: (i) a case in which a PCM is introduced in the mortar; (ii) a base case in that a regular mortar is considered. The two cases are subjected to simulate real temperature variation (summer and winter scenarios). Temperature difference of the "measurement point" showed that the heating/cooling system is turning on for a total of 7.83h under winter scenario for the base case, whereas the PCM case allowed a decrease in the heating time to 7.75h, which represents a 1.1% saving alone. In the case of summer scenario, the heating/cooling system is turning on for 5.5h per day in the base case, whereas the PCM case allowed a decrease in the heating time to 5h, which illustrates a 10% saving alone.
Keywords: demand response; demand side management; dynamic electricity tariff; heat storage; Smart building; fi=Energiatekniikka|en=Energy Technology|